Thin film (La0.7Sr0.3)0.95MnO 3-δ fabricated by pulsed laser deposition and its application as a solid oxide fuel cell cathode for low-temperature operation - Noh, H.-S.; Son, J.-W.; Lee, H.; Kim, H.-R.; Lee, J.-H.; Lee, H.-W. (2010)
The feasibility of using the thin film technology in utilizing lanthanum strontium manganite (LSM) for a solid oxide fuel cell (SOFC) cathode in a low-temperature regime is investigated in this study. Thin film LSM cathodes were fabricated using pulsed laser deposition (PLD) on anode-supported SOFCs with yttria-stabilized zirconia (YSZ) electrolytes. Although cells with a 1 μmthick LSM cathode showed poor low-temperature cell performance compared to that of a cell with a bulk-processed cathode due to the lack of a triple-phase boundary length, the cell with 200 nm-thick gadolinia-doped ceria (GDC) inserted between the LSM and YSZ showed enhanced performance and more stable operation characteristics in a comparison of a cell without a GDC layer. We postulate that the GDC layer likely improved the cathode adhesion, therefore contributing to the improvement of the cell performance instead of serving as an interfacial reaction buffer.
Keywords: Anode-supported SOFCs; Cell performance; Enhanced performance; Gadolinia doped ceria; Interfacial reactions; Lanthanum strontium manganite; Low temperatures; Low-temperature regime; Solid oxide; Stable operation; Thin film cathode; Thin-film technology; Triple phase boundary; Cerium compounds; Deposition; Lanthanum; Lanthanum alloys; Lanthanum oxides; Manganese oxide; Pulsed laser deposition; Solid oxide fuel cells (SOFC); Strontium; Thin films; Vapor deposition; Yttria stabilized zirconia; Zirconia; Pulsed lasers